Discriminación arancelaria y decisiones de localización de las empresas - Mendez, Jose (Estudios de Economía, 2016)
The purpose of this paper is to analyse the effects of economic integration amongcountries on firms investment decisions when such decisions are taken strategically.It is shown that, in this context, the traditional “tariff jumping” argumentis not always applicable and that localisation decisions depend on the existingrelationship between tariff discrimination and market size. It is argued thateconomic integration disincentives national firms market entry.